Analysis Of Financial Literacy And Parents' Socio- Economic Status On Investment Interest In The Capital Market - Virgiawan Bagus Satria Bismatama; Ulfi Pristiana, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to determine the influence of financial literacy and social status on investment interest in the capital market among students of the Faculty of Economics and Business at the University of 17 August 1945 Surabaya. Based on the objectives of this research, the researcher employed a descriptive quantitative research design using a survey method with structured questionnaires distributed to respondents. These questionnaires were designed to obtain specific information through questions or statements provided via Google Forms. The population consisted of students at the University of 17 August 1945 Surabaya. To determine the sample size, the Slovin formula was used. The data collection technique utilized was Accidental Sampling. The data analysis technique employed was multiple linear regression. The research results indicate that financial literacy does not have a significant influence on investment interest in the capital market among students, while social status has a significant influence on investment interest in the capital market among students of the Faculty of Economics and Business at the University of 17 August 1945 Surabaya.